EmotionPrism: a design tool that communicates 25 pleasurable human-product interactions. (2017) - Yoon, JungKyoon; Pohlmeyer, Anna E.; Desmet, Pieter M.A.
The range of positive emotions experienced in human-product interactions is multifarious. Differentiating positive emotions (e.g., joy, love, hope, and interest) and having an awareness of associated expressive interaction qualities (e.g., playful, careful, persistent and focused interaction) can support designers to influence users' interactions in a favourable way. This paper introduces the development and application of EmotionPrism, a tool for designers to gain a better understanding specific positive emotions and related expressive interaction qualities. EmotionPrism is a collection of movie-sets that represents 25 different positive emotions in dynamic hand-object interactions, combined with theoretical descriptions of the emotions. Designers can use the tool to envision and discuss what kinds of interactions would be appropriate or desirable to incite and to select a set of relevant positive emotions accordingly by referring to the set of information as a repertoire to choose from. The paper first describes characteristics of positive emotions with a focus on expressive behaviour and then discusses considerations for the tool development. The second section reports the process of developing the tool. Thirdly, we present the results of a design workshop in which the tool was used and evaluated.